Impact of the introduction of computerised physician order entry (CPOE) on the surveillance of restricted antimicrobials and compliance with policy. (16th November 2016) - Metcalfe, Julie; Lam, Alice; Lam, Skip S. H.; de Clifford, Jan‐Marie; Schramm, Petra
Abstract: Background: Prescribers at a 400‐bed metropolitan teaching hospital applied for approval to prescribe restricted antimicrobials using Guidance DS ® (GDS), an electronic antimicrobial approval system (EAAS). The implementation of Cerner Millennium ® (CM), a computerised physician order entry system (CPOE), necessitated a new but cumbersome workflow for prescribers. This prompted an evaluation of the value of a stand‐alone EAAS, which has no interface with a CPOE, for antimicrobial stewardship. Aim: This study compares the performance of an EAAS and CPOE, used alone and in combination, for surveillance of restricted antimicrobials and compliance with antimicrobial restriction policy. Method: General medical and surgical patients prescribed restricted antimicrobials over three defined periods were retrospectively recruited; period one (P1) used GDS plus National Inpatient Medication Chart, period two (P2), GDS plus CM, and period three (P3), CM alone. For each period, 100 medical and 100 surgical restricted antimicrobial orders were collected. Data collection included prescribing date, indication, approvals obtained, and time to approval. Surveillance rate and compliance was compared. Results: The introduction of CM improved surveillance from 10.5% (P1) to 65% (P2) and 100% (P3) via a CM reporting module (p < 0.0001). Compliance improved from 6% (P1), to 55% (P2) and 76% (P3) (p < 0.0001). Documentation of a clear/complete indication improved from 10% (P1) to 56.5% (P2) and 76.5% (P3) (p < 0.0001). Approvals obtained within 24 h of prescribing improved from 61.9% (P1), to 96.9% (P2), and 100% (P3). Conclusion: Cerner Millennium ®, with customisation, optimises surveillance and significantly improves compliance with policy, negating the need for a stand‐alone EAAS.